2003
DOI: 10.3141/1820-09
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Containerized Grain and Oilseed Exports: Industry Profile

Abstract: Diversification of production agriculture has received much attention in recent years. As producers and customers adapt to technologically advanced production and marketing systems, it is important to consider opportunities available for adding value to raw grain through alternative handling and transportation options. One such opportunity that has been more widely recognized in recent years is marketing grain products via container. It has been estimated that this option is currently used in marketing about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to statistics from the U.S. Department of Transportation presented in Vachal and Reichert (20), there are more than 2,695 intermodal facilities in the United States, providing more flexible access to producers and buyers. These facilities also play integral roles in containerized commodity trade, which adds value to agricultural products such as soybeans through their ease of transition between modes of transportation in international trade (20).…”
Section: Brazilian and Us Soybean Transportation Policies And Issuesmentioning
confidence: 99%
“…According to statistics from the U.S. Department of Transportation presented in Vachal and Reichert (20), there are more than 2,695 intermodal facilities in the United States, providing more flexible access to producers and buyers. These facilities also play integral roles in containerized commodity trade, which adds value to agricultural products such as soybeans through their ease of transition between modes of transportation in international trade (20).…”
Section: Brazilian and Us Soybean Transportation Policies And Issuesmentioning
confidence: 99%
“…Hence, it is not possible for any of them to have negligible farm‐level exports when compared to the other U.S. states. Vachal and Kortie (2019) reported on North Dakota's grain and oilseed shipments, revealing higher values compared to the export values obtained from the USDA FAS.…”
Section: Introductionmentioning
confidence: 93%
“…Later, Prentice studied on re-designing the grain logistics chain in Canada by replacing bulk handling with containerization and concluded that technological advances in information collection and transmission have already made container shipment a rival to the bulk handling of grain. Vachal and Reichert (2002) and Vachal et al (2003) explored the trends in the containerized movement of grain and general logistics information, in an attempt to find out factors for successful container shipment, such as costs, services and logistical alternatives. Vachal et al (2004) then studied the export of containerized grain and oilseed in USA and proposed that technological advances, privatization of foreign markets and the declining transaction costs on the global market have facilitated the diversification of container industry in niche markets, such as the development of small-volume containerized products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another finding from the study of Prentice (1998) was that the container system could shorten the transport time significantly compared to the bulk system. Vachal and Reichert (2003) applied an economic decision model to illustrate potential cost differences in the identity preserved and generic marketing of raw grain. The economic decision model is based on a spreadsheet simulation of individual transportation and marketing costs.…”
Section: Economics Analysismentioning
confidence: 99%